Desarrollo y comparación de métodos de medición de perfiles de altura considerando su impacto en el consumo de vehículos eléctricos (2017)
The objective was to find a measurement methodology that could be easily replicated to measure the height profiles and slopes of the terrains in which the electric cars are tested in order to be able to determine by means of mathematical models the energy consumed by it. To this end, a circuit was chosen in the city of Bogota where it was easy to carry out a topographic survey that would serve as a reference to compare other simpler measurement methods. The methods chosen to be compared were: A survey of the circuit by walking with a barometric sensor (cycling and walking), lifting the tilt profile by means of an inclinometer (static and dynamic). Once all the measurements were made, all the data processing was done to obtain the slope profiles found with all the methodologies (including the topographic reference) to be compared. With the tilt profiles, a simulation was performed...